Iron Deficiency Anaemia with Underlying Beta-Thalassemia Carrier in a Single Mother with Multiple Substance Abuse: A Case Report - Idris, Mohd Faznynell; Rashid, Aneesa Abdul (International Journal of Human and Health Sciences (IJHHS), 2025)
Anemia in pregnancy is a common non-communicable condition in primary care, where severe anemia, particularly when associated with comorbidities, requires prompt intervention. This case report describes a 23-year-old single mother with a history of substance abuse and smoking, who was diagnosed with severe iron deficiency anemia during late pregnancy. Despite being asymptomatic, her anemia led to hospital admission, where she required transfusions and iron therapy. Her substance abuse further complicated medical management. The case outlines her obstetric history, social challenges, and the complexities of providing care. During a subsequent hospital admission, she experienced postpartum hemorrhage, necessitating urgent intervention. Further investigations revealed that she carried the beta-thalassemia trait, prompting the need for family screening. This case underscores the importance of a multidisciplinary approach in managing complex medical conditions during pregnancy and postpartum, especially in high-risk populations. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S39